Detection of Quercitrin Compound of Scurrula atropurpurea using Chromatographic Method - Arkham, Muhammad Nuzul; Santosa, Djoko; Fakhrudin, Nanang (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Mistletoe (Scurrula atropurpurea) is a semi-parasitic plant whose growth depends on host plants. Mistletoe is often considered harmful; however, from a scientific perspective, it has potential as a source of bioactive compounds with pharmacological benefits. This study explores the secondary metabolites of S. atropurpurea growing on Lagerstroemia speciosa trees, with the aim of detecting and identifying quercitrin compounds through chromatography and evaluating their activity in scavenging DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals. Mistletoe samples were collected, washed, dried at 50°C, ground, and then extracted. The extract was partitioned with n-hexane and ethyl acetate, the ethyl acetate fraction was then fractionated with Vacuum Liquid Chromatography (VLC) using n-hexane:ethyl acetate and 100% methanol as the mobile phase, yielding nine fractions. Preliminary analysis was performed by Thin-Layer Chromatography (TLC) using n-hexane:ethyl acetate (8:2, 4:6) and n-hexane:ethyl acetate: formic acid (2:7.5:0.5) as mobile phases. Further identification was performed using High-Performance Liquid Chromatography (HPLC) with a gradient mobile phase of acetonitrile: trifluoroacetic acid + aquadest (10:90, 20:80, 25:75, 18:82). The fractions obtained were then tested for their activity in scavenging DPPH free radicals. TLC results showed that the extract and fractions H and I had an hRf value of 51.2, comparable to the quercitrin standard. HPLC analysis indicated retention times for fraction H (14.819 minutes) and fraction I (14.936 minutes) that were consistent with the standard. The UV spectra of both fractions displayed two characteristic quercitrin peaks at 254 nm and 348 nm. The DPPH assay showed IC₅₀ values of 20.37 µL/mL for fraction H and 22.54 µL/mL for fraction I, both of which are classified as very strong. The result of this study confirms the presence of quercitrin in S. atropurpurea and demonstrates the significant antioxidant potential of this compound.